Analysis of ventilation rate and concentrations of carbon dioxide in the office - Kapalo, P. (Видавництво Львівської політехніки, 2013)
The aim of the article is to establish the necessary air exchange rate in the room at the principal production carbon dioxide calculation and experiment. In order to determine the necessary volume the air flow was made more experimental measurements in selected rooms. From the measured data of concentration CO2 by combination of graphic method and mathematical formulas we can determinate the required air flow which meets the hygiene requirements. The entire computation we can see on the example. Метою статті є встановлення необхідного рівня кратності повітрообміну в приміщенні на основі розрахунків концентрації вуглекислого газу та експериментально. Для встановлення необхідного об’єму потоку повітря були зроблені експериментальні заміри у обраних приміщеннях. З виміряних даних щодо концентрації CO2 у комбінації з графічною методикою та математичними формулами можна визначити необхідну кратність повітрообміну, що задовольняє гігієнічні вимоги. Розрахунок супроводжується прикладом.
Keywords: concentration of carbon dioxide; ventilation; flow; концентрація вуглекислого газу; вентиляція; потік